Konsep Agama dan Makna Islam (Islam sebagai Agama Wahyu yang Benar dan Final, serta Islam sebagai Pemikiran dan Peradaban) - Nuruddin, Nuruddin; Sumiran, Sumiran (TSAQOFAH, 2025)
This article discusses the concept of religion from an Islamic perspective, emphasizing Islam as a true and final revealed religion (agama wahyu) as well as a comprehensive system of thought and civilization. Islam is understood not merely as a spiritual belief, but as an all-encompassing way of life that governs every aspect of human existence, both individual and societal. The purpose of this study is to analyze Islam as an integral din through philosophical and theological approaches. Utilizing a descriptive qualitative method based on literature review, the article highlights two main dimensions of Islam: the transcendental, as divine revelation conveyed through Prophet Muhammad (SAW) as the final messenger; and the historical, as a dynamic civilization that has fostered the development of science, culture, and social order. Islam, as a perfect religion, requires no revision yet remains profoundly relevant in addressing contemporary challenges. The conceptual distinction between its transcendental and historical aspects affirms Islam’s flexibility in facilitating social transformation grounded in divine values. The findings affirm that Islam is an integral, transformative, and contextual din that serves as a comprehensive path of life for humanity.